2015
DOI: 10.18052/www.scipress.com/ilcpa.59.10
|View full text |Cite
|
Sign up to set email alerts
|

Growth Responses of Okra (<i>Albemoschus esculentus)</i> and Jute Mallow (<i>Corchorus oitorius)</i> to Water Stress and Non-Water Stress Conditions

Abstract: ABSTRACT. Water stress is one of the abiotic stress factors that affect establishment, growth and yield of crop. Therefore, a screen house study was carried out to determine the effect of water stress on growth and yield of Okra and Jute mallow. 7 litre capacity each bucket was filled with 10 kg of soil and arranged in a completely randomized design with three replicates. There were four irrigation regimes based on field capacity; 100% FC (control), 75% FC, 50% FC, and 25% FC Seeds from local source were sown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
2
0
0
Order By: Relevance
“…In this investigation, reduced plant height was recorded in the severe drought in all three okra cultivars. These cultivars were compared to their respective controls and these findings agree with similar research by Ewetola and Fasnami 16 , who reported plant height reduction in okra plants subjected to 25% field capacity of water as compared to plants under 75% field capacity of water. Current results also agreed with Wu et al 17 , who found out that plant height in water-stressed citrus seedlings was reduced up to 25%.…”
Section: Discussionsupporting
confidence: 89%
“…In this investigation, reduced plant height was recorded in the severe drought in all three okra cultivars. These cultivars were compared to their respective controls and these findings agree with similar research by Ewetola and Fasnami 16 , who reported plant height reduction in okra plants subjected to 25% field capacity of water as compared to plants under 75% field capacity of water. Current results also agreed with Wu et al 17 , who found out that plant height in water-stressed citrus seedlings was reduced up to 25%.…”
Section: Discussionsupporting
confidence: 89%
“…In both varieties, the highest reduction in leaf number, branches, and leaf area were recorded in the acute moisture stress condition. Similar results were also found by Ewetola and Fasanmi [ 27 ] in C. olitorius plants where at four different moisture levels (100, 75, 50, and 25% FC), they recorded the highest plant height, stem girth, and leaf area at 75% FC and the lowest at 25% FC, corresponding to the control. At 75% FC, a five-fold increase in biomass yield was observed compared to the control.…”
Section: Jute Responses To Abiotic Stresssupporting
confidence: 89%